Comparative Study on the Phytochemical and Micronutrients Levels in Selected Edible Mushroom Samples - Abah, Moses Adondua; Adebisi, Arowora Kayode; Moses, Iyekekpolor Osamudiame; Dooshima, Arowora Mercy; Umaru, Isaac John; Uchechukwu, Ukoh Daniel; Timothy, Mgbede (African Journal of Biochemistry and Molecular Biology Research, 2024)
Edible mushrooms have been known to possess various phytochemical and micro nutrient levels. Edible mushrooms can be eaten and they supply nutritional benefits to the human body system. It is not widely consumed mainly due to paucity of information about it. Therefore, this research was conducted to compare the phytochemicals and micronutrients levels in two selected edible mushrooms (Pleurotus ostreatus and Agrocybe aegerita). Fully matured mushroom species of Oyster and Tea tree mushroom were collected, air dried and then stored in transparent polythene bags. Quantitative determination of phytochemicals and micronutrients (minerals and vitamins) present was carried out. Tea tree mushroom used in this research can be said to have the higher concentration of phytochemicals (phenols and poly-phenols), as there was no significant difference (p>0.05) in Oyster mushroom in comparison to Tea tree mushroom for phenols and poly-phenols. The results obtained from this research indicated that there was no significant decrease(p>0.05) in Oyster mushroom in comparison to Tea tree mushroom for Sodium, Iron, Magnesium, Selenium, Manganese. While there was a non-significant increase (p>0.05) in Oyster mushroom in comparison to Tea tree mushroom for Potassium, Calcium, Phosphorus, Copper. Tea tree mushroom had higher composition of vitamins A and C than oyster mushroom which were not significantly different (p>0.05). The findings in this study revealed that Tea tree mushroom (Agrocybe aegerita) is slightly better than Oyster mushroom (Pleurotus ostreatus) based on their phytochemicals and micronutrients (minerals and vitamins).